PROMOTIONAL EFFECTIVENESS AND PRODUCT QUALITY ON CUSTOMER SATISFACTION AT DEKORINDO JAYA FURNITURE GUNUNGSITOLI - Marletare Daeli; Yuterlin Zalukhu; Edward Harefa (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
A person may experience either positivity or despondency after assessing a product in light of the expectations the person had for it, which is known as satisfaction. The objective of this research was to investigate, from a multiracial perspective and, at the same time, the impact that Dekorindo Jaya Furniture's marketing efforts and promotional strategies had on the level of contentment experienced by its clientele. This study was carried out in Dekorindo Jaya Furniture, which is located in Gunungsitoli City, North Sumatra. Using the nonprobability sampling method, the number of samples was decided to be 45 respondents, and multiple regression was implemented to analyze the data. According to the findings of the research conducted, it was discovered that advertising and product quality have a favorable and significant effect on customer satisfaction at Dekorindo Jaya Furniture Gunungsitoli, and this holds true for customers of both races concurrently. The findings of this investigation point to the recommendation of analyzing additional policies and tactics for advertising products and product quality to ensure customer satisfaction.